Dominasi Pertumbuhan Laba : Tinjauan Important Performance Analisys di (3) Tiga Perusahaan Sentrafood di Indonesia - Sukma Dewi; Abdullah Abdullah; Pra Gemini (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research is based on a problems that occur in centrafood companies where the net profit margin has increased and profit growth has decreased. has increased and profit growth has decreased, The discrepancy with the theory is an interesting phenomenon to be studied further about profit growth. further about profit growth. This research uses a quantitative method, with a population of 8 companies with quantitative method, with a population of 8 companies with purposive sampling techniques using 3 criteria so that the The sampling technique uses 3 criteria so that a sample of 3 companies is obtained. The research results found are the four indicators of the profitability ratio have a significant influence on profit growth. profitability ratio has a significant effect on profit growth, However, when viewed from the t-statistics, there are two that have a very strong influence, namely Return on Assets on profit growth. which are very strong, namely Return on Assets on profit growth with a value of 3.464478 and Return on Equity with a value of -9.512826. furthermore, in the IPA analysis, it was found that ROA has a significant level of profit growth. IPA analysis found that ROA has the best level of suitability, it is concluded that high and low profits can be caused by good asset turnover with a minimum level of equity value, even though the company has a minimum level of equity value. The minimum level of equity value, even though the company gets high profitability but if the even though the company gets high profitability, but if the equity value is high, it will reduce the company's cash which results in profit growth. will reduce the company's cash which results in decreased profit growth. Translated with DeepL.com (free version)